2014
DOI: 10.1161/circgenetics.113.000448
|View full text |Cite
|
Sign up to set email alerts
|

Sarcomere Mutation-Specific Expression Patterns in Human Hypertrophic Cardiomyopathy

Abstract: Background Heterozygous mutations in sarcomere genes in hypertrophic cardiomyopathy (HCM) are proposed to exert their effect through gain-of-function for missense mutations or loss-of-function for truncating mutations. However, allelic expression from individual mutations has not been sufficiently characterized to support this exclusive distinction in human HCM. Methods and Results Sarcomere transcript and protein levels were analyzed in septal myectomy and transplant specimens from 46 genotyped HCM patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
128
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(142 citation statements)
references
References 48 publications
12
128
2
Order By: Relevance
“…First, the minigene splice assay may not identify the precise splice alteration that occurs in vivo. However, of the 53 splice-altering variants identified here, 16 variants were independently characterized by RT-PCR in patient tissues (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25), alter splicing, and are pathogenic (Table S3). Moreover, the fact that 48 of 53 VUS were identified in patients with an AD cardiomyopathy provides a very strong likelihood that the aberrant splicing observed in the minigene assay occurs in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…First, the minigene splice assay may not identify the precise splice alteration that occurs in vivo. However, of the 53 splice-altering variants identified here, 16 variants were independently characterized by RT-PCR in patient tissues (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25), alter splicing, and are pathogenic (Table S3). Moreover, the fact that 48 of 53 VUS were identified in patients with an AD cardiomyopathy provides a very strong likelihood that the aberrant splicing observed in the minigene assay occurs in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, however, physiological stimuli and comorbidities seem to exert a modest impact especially on the phenotypic expression of HCM. Future research targeting HCM variability should rather focus on molecular aspects including modifier genes, epigenetic factors, and the role of regulatory systems such as microRNAs, the ubiquitine‐proteasome complex, or nonsense‐mediated RNA decay 78, 79…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that truncation mutations in cMyBP-C diminish the total protein level and cause hypertrophic cardiomyopathy through haploinsufficiency [36][37][38]. However, a recent study suggests that consequences of the mutations cannot be predicted solely based on the type or location of the mutation [33]. Our in vitro results showed that full length cMyBP-C protein level was not significantly altered between wild-type, single mutations and double mutation, indicating that both mutant mRNA and protein are stable and UPS is unlikely to be involved in the regulation of mutant protein clearance in H9C2 cells.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to examine the expression and stability of the single and double point mutations as a recent study showed complexity in the expression of point mutations [33]. To determine the isolated effect of E258K, E441K and their combination (E258K-E441K) on protein stability, we transfected H9C2 cells with WT or single or double mutation of MYBPC3 constructs tagged with GFP.…”
Section: Stability Of Expressed Mutant Proteins In Mammalian Cellsmentioning
confidence: 99%